Changes in Liver Mechanical Properties and Water Diffusivity During Normal Pregnancy Are Driven by Cellular Hypertrophy - Garczyńska, Karolina; Tzschätzsch, Heiko; Kühl, Anja A.; Morr, Anna Sophie; Lilaj, Ledia; Häckel, Akvile; Schellenberger, Eyk; Berndt, Nikolaus; Holzhütter, Hermann-Georg; Braun, Jürgen; Sack, Ingolf; Guo, Jing (Frontiers in Physiology, 2020)
During pregnancy, the body’s hyperestrogenic state alters hepatic metabolism and synthesis. While biochemical changes related to liver function during normal pregnancy are well understood, pregnancy-associated alterations in biophysical properties of the liver remain elusive. In this study, we investigated 26 ex vivo fresh liver specimens harvested from pregnant and nonpregnant rats by diffusion-weighted imaging (DWI) and magnetic resonance elastography (MRE) in a 0.5-Tesla compact magnetic resonance imaging (MRI) scanner. Water diffusivity and viscoelastic parameters were compared with histological data and blood markers. We found livers from pregnant rats to have (i) significantly enlarged hepatocytes (26 ± 15 %, p < 0.001,), (ii) increased liver stiffness (12 ± 15 %, p = 0.012), (iii) decreased viscosity (-23 ± 14 %, p < 0.001), and (iv) increased water diffusivity (12 ± 11 %, p < 0.001). In conclusion, increased stiffness and reduced viscosity of the liver during pregnancy are mainly attributable to hepatocyte enlargement. Hypertrophy of liver cells imposes fewer restrictions on R1.7.1 intracellular water mobility, resulting in a higher hepatic water diffusion coefficient. Collectively, MRE and DWI have the potential to inform on structural liver changes associated with pregnancy in a clinical context.